EJMM 2021
DOI: 10.51429/ejmm30217
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii as a possible risk factor for COVID-19 severity: a case-control study

Abstract: Background: COVID-19 is a worldwide pandemic that stroke almost all countries of the world causing thousands of deaths and disabilities and burdened the economy of countries. One of the main criteria of the immune response against COVID-19 is the “immune exhaustion”, due to increased expression of T cell suppressor molecules e.g. programmed death-1 (PD-1), that leads to flaring of viral multiplication and disastrous clinical outcomes. This immune exhaustion is not restricted to COVID-19 but is also a common co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…However, in another study, Sharaf-El-Deen demonstrated that the prevalence of toxoplasmosis was significantly higher in patients with COVID-19 (admitted to the Isolation Department of Shibin El-Kom Hospital, Egypt) than in healthy individuals. Their findings also showed the number of T. gondii positive cases was statistically significantly higher in the severe patient group compared with the moderate group [ 28 ]. In a study from the north of Iran, Ghaffari et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, Sharaf-El-Deen demonstrated that the prevalence of toxoplasmosis was significantly higher in patients with COVID-19 (admitted to the Isolation Department of Shibin El-Kom Hospital, Egypt) than in healthy individuals. Their findings also showed the number of T. gondii positive cases was statistically significantly higher in the severe patient group compared with the moderate group [ 28 ]. In a study from the north of Iran, Ghaffari et al .…”
Section: Discussionmentioning
confidence: 99%
“…The studies' quality was evaluated using the JBI Critical Appraisal Tools for cross-sectional research. All the studies were of moderate quality (Table S3) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Egger's test for the evaluation of publication bias obtained a value of p = 0.4301 (t = 0.82, df = 11).…”
Section: Quality Of the Included Studies And Publication Biasmentioning
confidence: 99%
“…Reactivation of latent toxoplasmosis has been reported in a number of patients who received immunosuppressive therapy, such as corticosteroids [154][155][156][157][158], JAKs inhibitors [159,160], TNF-α blockers [161][162][163] and IL-17A blockers [164], and the most common sequels were ocular [154][155][156][160][161][162] and cerebral [157][158][159]163] toxoplasmosis. In a case-control study among 100 COVID-19 patients in Egypt, a significantly higher prevalence of toxoplasmosis was detected among mild to moderate COVID-19 patients than the healthy control group [165]. Indeed, T. gondii seropositive cases exhibited a significant increase in lymphocytic expression of programmed death-1 (PD-1), which is a marker that correlates with proinflammatory status.…”
Section: Toxoplasmosismentioning
confidence: 99%